PENAMPILAN PERTUMBUHAN DAN HASIL LIMA HIBRIDA TOMAT PADA LAHAN ULTISOL DAN GAMBUT - Elpiana Purba; Alnopri Alnopri; Bandi Hermawn; Helfi Eka Saputra (BPFP Universitas Bengkulu, 2020)
[GROWTH APPEARANCE AND YIELD OF FIVE TOMATO HYBRIDS ON ULTISOL AND PEATLANDS]. Ultisol and peat are included in marginal land that can support the growth and development of plants. This study was aimed to compare the growth and yield of five tomato hybrids on ultisol and peatlands. The experiments were carried out in the field with the soil type of on ultisol and peats. The experiment was arranged in a Randomized Completely Block Design with 3 replications. The hybrids evaluated were UNB-1 × UNB-2, UNB-3 × UNB-1, UNB-2 × UNB-1, and UNB-2 × UNB-3, and Sinta as a control hybrid. The results showed that in ultisol lands, the diversities among genotypes were observed in some variables, including the age of flowering, a number of fruits per plant, fruit diameter, fruit weight per plant, and fruit sweetness level. On the peatlands, a significant diversity was observed in plant height, age of flowering, age of harvest, fruit weight per plant, number of flowers per bunch. Based on this evaluation in the Ultisol soil, the yield of UNB2 × UNB1 was higher than control (Sinta genotype), whereas, in peat, the growth and yield components of UNB2 × UNB3 is the best and Sinta hybrid as a control genotypes showed the highest yield among other genotypes.